Ulcerative colitis in association with Takayasu's disease. - Chapman, R; Dawe, C; Whorwell, P; Wright, R (1978)
A case of total ulcerative colitis associated with large-vessel disease consistent with a diagnosis of Takayasu's disease is described in a 21-year-old Pakistani female. The possible relationship between the two disorders is discussed.